Pemanfaatan Ekstrak Buah Kaktus (Oputian elatior Mill.) sebagai Pewarna Alami pada Sediaan Lipstik - Nuur Aanisah; Evi Sulastri; Yusriadi Yusriadi; Friskilla Friskilla; Armini Syamsidi (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Cactus fruit (Opuntia elatior Mill) is a flowering plant of the Cartacae family, which grows in high and dry plateau known to contain betacyanin compound, which is a natural dye of red color. The aim of this research is to identify the physical and chemical characteristics of betacyanin extract of cactus fruit on lipstick ingredients. The examination of physical and chemical characteristics includes organoleptic testing, homogeneity, melting point, pH, lipstick smearing, lipstick hardness and betacyanin levels in the lipstick. Observations were made on the first day and the seventh day of storage. The test results show red lipstick ingredients with a distinctive aroma of the betacyanin extract and densely dispersed homogenous texture. Meanwhile, the melting point test showed lipsticks melt at the temperature of 70°C, with pH value of the first day is 5,86 and the seventh day that is 6,13, polishing evenly and obtained lipstick 90g lipstick hardness level. The result of betacyanin content on the first day is 0.195 mg / 100gram, and on the seventh day is 0.105 mg / 100gram. In conclusion, lipstick produce with betacyanin extract of cactus fruit has good physical stability in accordance with SNI 16-4769-1998 about the ingredients of lipstick (Indonesian National Standard).